2009
DOI: 10.5194/bg-6-309-2009
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of ammonia exchange with cut grassland: strategy and implementation of the GRAMINAE Integrated Experiment

Abstract: Abstract.A major international experiment on ammonia (NH 3 ) biosphere-atmosphere exchange was conducted over intensively managed grassland at Braunschweig, Germany. The experimental strategy was developed to allow an integrated analysis of different features of NH 3 exchange including: a) quantification of nearby emissions and advection ef- The prior analysis established the spatial and temporal design of the experiment, allowing significant synergy between these objectives. The measurements were made at 7 me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 118 publications
2
41
0
Order By: Relevance
“…The European project GRAMINAE (Grassland Ammonia Interactions Across Europe - Sutton et al, 2001Sutton et al, , 2009a, was instigated to quantify exchange of NH 3 with grasslands along an East-West transect across Europe. As part of this effort, an integrated experimental campaign took place 18 May-15 June 2000 at a 6.4 ha experimental agricultural grassland of the German Federal Agricultural Research Centre Braunschweig, Völkenrode (52 • 18 N, 10 • 26 E; 79 m a.s.l.…”
Section: Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The European project GRAMINAE (Grassland Ammonia Interactions Across Europe - Sutton et al, 2001Sutton et al, , 2009a, was instigated to quantify exchange of NH 3 with grasslands along an East-West transect across Europe. As part of this effort, an integrated experimental campaign took place 18 May-15 June 2000 at a 6.4 ha experimental agricultural grassland of the German Federal Agricultural Research Centre Braunschweig, Völkenrode (52 • 18 N, 10 • 26 E; 79 m a.s.l.…”
Section: Experimental Datamentioning
confidence: 99%
“…Agronomic conditions in the experiment are described by Sutton et al (2009a, b) and show a large range of situations to evaluate the model: a) the vegetation was at first tall and dense; b) it was cut on 29 May 2000, and then left for 3 days; and c) the field was fertilized on 6 June with 108 kg N ha −1 as calcium ammonium nitrate. The calendar events are summarized in Fig.…”
Section: Experimental Datamentioning
confidence: 99%
“…This ground-level source was believed to be responsible for the sustained NH 3 emissions observed after grass cutting, as indicated by independent bioassay and chamber measurements (David et al, 2009). The GRassland AMmonia Interactions Across Europe (GRAMINAE) grassland experiment, summarised by Sutton et al (2009a, b), demonstrated that overall, net above-canopy fluxes were mostly determined by stomatal and cuticular uptake before the cut, by leaf litter emissions after the cut, and by fertilizer and litter emissions after fertilization.…”
Section: Recapture Of Soil/litter-emitted Nh 3 By the Overlying Canopymentioning
confidence: 99%
“…The magnitude was achieved by using a g value of 80 000 following leaf fall, which is in the range of values found for senescing plant material (e.g. Sutton et al, 2009), but larger than measurements of the litter emission potential established by Wang et al (2011) during the previous autumn. In the absence of in-canopy turbulence measurements, the parameterisation of the in-canopy transport resistance is poorly constrained.…”
Section: Lai and Nh 3 Fluxes In The Leaf Fall Periodmentioning
confidence: 99%